Primary Fallopian Tube Carcinoma: Results of a Single-Institutional Retrospective Analysis of 17 Patients with Evaluation of Staging and Prognostic Factors - Neserine Tounsi; Hanen Bouazize; Ikram Margheli; Nadia Boujelbene; Hechiche Monia; Maher Slimane; Khaled Rahel (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Primary carcinoma of the fallopian tubes is one of the less common gynecological cancers. It constitutes (0.14-0.18%) of gynecological malignancies. Our study aimed to review the managing process of primary carcinoma of the fallopian tubes in the mono-center institute and to identify prognostic factors impacting survival.